High inductive magnetic stimuli and their effects on mesenchymal stromal cells, dendritic cells, and fibroblasts - Průcha, J; Skopalik, J; Justan, I; Parák, T; Gabrielová, E; Hána, K; Navrátil, L (Physiological research, 2019)
Effects of low-frequency electromagnetic fields (LF EMF) on the activation of different tissue recovery processes have already been fully understood. Preliminary recent data demonstrated that a special case of sinusoidal electromagnetic fields, known as amplitude-modulated currents (AMC) could have a potential to accelerate the cell metabolism or cell migration. An AMC generator was designed to generate sinusoidal induced electric currents with the amplitude modulation and the harmonic carrier frequency of 5,000 Hz was modulated by frequencies of 1 to 100 Hz. The magnetic field peak was 6 mT, electric field intensity 2 V/m and the current density of induced electrical currents was approximately 1 A/m(2). The coil of the generator was adapted to easy handling and safe integration into the shelf of the CO(2) incubator. The shelf with the coil was prepared for the introduction of cells in standard plastic in vitro chambers. The tests focused on cells with migratory capacity after injury or during immunological processes and thus, mesenchymal stromal cells (MSC), dendritic cells (DC), and fibroblasts were chosen. The tests involved exposures of the cells to LF EMF (180 min/day) every day, for a period of three days, before examining them for cell death, morphology changes, and CD markers. The samples were tested by using MTT assay and the effects on the intracellular concentration of reactive oxygen species were quantified. The cell migration was finally measured with the help of the transwell migration assay. None of the cell types showed any decrease in the cell viability after the LF EMF application and the cells displayed minimum changes in reactive oxygen species. Functional changes (acceleration of cell migration) after AMC exposure were statistically significant for the MSC samples only. The acceleration of MSCs is associated with the production of MMP by these cells. The EMF has a potential to be a safe, clinically applicable selective activator of MSC homing, MSC paracrine production, and subsequent regeneration processes.
Keywords: myši; Electromagnetic Fields; Mesenchymal Stem Cells; Humans; Fibroblasts; Paracrine Communication; fibroblasty; lidé; elektromagnetická pole; Cell Movement; 3T3 Cells; buňky 3T3; Dendritic Cells; Animals; matrixová metaloproteinasa 2; parakrinní signalizace; zvířata; pohyb buněk; Mice; dendritické buňky; mezenchymální kmenové buňky; Matrix Metalloproteinase 2